Invisible Britain : portraits of hope and resilience - Sng, Paul (Policy Press, 2018)
Invisible Britain: Portraits of Hope and Resilience is a photographic ethnography book that features the stories and portraits of individuals across the UK who have been impacted by social issues such as austerity, Brexit, deindustrialisation, nationalism and cuts to public services. The book captures and shares 40 untold stories of hope and resilience from a diverse range of people, many of whom feel misrepresented in the media and out of sync with the government and politicians. Each story will is told in the individual's own words and is accompanied by a portrait from an accomplished documentary photographer.